Determinants of prepaid systems of healthcare financing: A worldwide country-level perspective - Andrea M. Leiter; Engelbert Theurl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
In this paper we examine determinants of prepaid modes of health care financing in a worldwide cross-country perspective. We use three different indicators to capture the role of prepaid modes in health care financing: (i) the share of total prepaid financing as percent of total current health expenditures, (ii) the share of voluntary prepaid financing as percent of total prepaid financing, and (iii) the share of compulsory health insurance as percent of total compulsory financing arrangements. We refer to a panel data set comprising 158 countries and covering the time period 2000-2015. We apply a static as well as a dynamic panel data model. We find that the current structure of prepaid financing is significantly determined by its different forms in the past. The significant influence of governmental revenues, development assistance for health and regulatory quality varies depending on the financing structure we look at. The country's GDP per capita, the agricultural value added, the degree of urbanization and the share of the elderly are only of minor importance for explaining the variation in a country's structure of health care financing. From our analysis we conclude that more detailed information on indicators which reflect the distribution of individual characteristics (such as income and health risks) within a country's population would be needed to gain deeper insight into the decisive determinants for prepaid health care financing.
Keywords: I13; I14; H51; C33; 330; Health care financing; prepaid health care financing systems; out-of-pocket payments; panel data analysis